The Role of the Madrasah Principal in Improving the Quality of Graduates at NU Banat Madrasah Aliyah, Kudus Regency - Aulia, Maulidiah; Tri Handayani (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study examines the role of the madrasah principal in enhancing the quality of graduates at NU Banat Madrasah Aliyah, Kudus Regency. The research is motivated by the urgent need to improve graduate outcomes as part of a complex and continuous educational process. Specifically, the study aims to describe the principal’s role as a leader, manager, and innovator in strengthening graduate quality. Using a qualitative case study approach, data were collected through observation, interviews, and documentation, and analyzed using the stages of data reduction, display, and conclusion drawing. The findings reveal three main roles of the principal. First, as a leader, the principal demonstrates discipline, active supervision of teachers and students, and continuous professional guidance through training and two-way communication. Second, as a manager, the principal designs comprehensive program planning, assigns tasks according to teacher competence, and manages administration, student affairs, infrastructure, and finances professionally, including the implementation of the ISO 9001:2015 quality system. Third, as an innovator, the principal initiates contemporary learning programs such as Integrated Tahfidz, Muhadasah, Conversation Class, project-based learning, and digital learning. These roles synergistically foster graduates who excel academically, spiritually, in character, life skills, and technological competence. This study contributes to the discourse on educational leadership by highlighting the strategic role of madrasah principals in improving graduate quality within Islamic educational institutions.